2011
DOI: 10.1007/s11916-011-0210-6
|View full text |Cite
|
Sign up to set email alerts
|

Latent Myofascial Trigger Points

Abstract: A latent myofascial trigger point (MTP) is defined as a focus of hyperirritability in a muscle taut band that is clinically associated with local twitch response and tenderness and/or referred pain upon manual examination. Current evidence suggests that the temporal profile of the spontaneous electrical activity at an MTP is similar to focal muscle fiber contraction and/or muscle cramp potentials, which contribute significantly to the induction of local tenderness and pain and motor dysfunctions. This review h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 48 publications
3
89
0
2
Order By: Relevance
“…229 Inactivation of latent trigger points with dry needling or with manual pressure techniques may prevent the development of active trigger points and reduce and in many cases remove their nociceptive input, normalize the synaptic efficacy, and reduce peripheral and central sensitization. 60 After eliciting a local twitch response with a needle, SP and CGRP were significantly reduced in active trigger points, which corresponds with the clinically observation of an immediate decrease in pain and local tenderness after the inactivation of a trigger point with dry needling. 10,11 We already mentioned that dry needling can restore range of motion and muscle activation patterns, 5,8,9 and reduce local, referred, and widespread pain.…”
Section: Dry Needling and Trigger Pointssupporting
confidence: 74%
See 1 more Smart Citation
“…229 Inactivation of latent trigger points with dry needling or with manual pressure techniques may prevent the development of active trigger points and reduce and in many cases remove their nociceptive input, normalize the synaptic efficacy, and reduce peripheral and central sensitization. 60 After eliciting a local twitch response with a needle, SP and CGRP were significantly reduced in active trigger points, which corresponds with the clinically observation of an immediate decrease in pain and local tenderness after the inactivation of a trigger point with dry needling. 10,11 We already mentioned that dry needling can restore range of motion and muscle activation patterns, 5,8,9 and reduce local, referred, and widespread pain.…”
Section: Dry Needling and Trigger Pointssupporting
confidence: 74%
“…58,59 Several studies have shown, however, that latent trigger points do provide nociceptive input into the dorsal horn even though they are not spontaneously painful. [60][61][62][63][64][65][66] It is not entirely clear why this occurs.…”
Section: Active and Latent Myofascial Trigger Pointsmentioning
confidence: 99%
“…38 Similar occurrence of referred pain following intramuscular injection of glutamate into latent MTPs and non-MTPs suggests that the dose of .2 mL, 1M glutamate is adequate for the activation of normal muscle nociceptors. A larger referred pain area in the latent MTP group than in the normal muscle point group (non-MTP) following the same nociceptive stimulation consolidates the concept that muscle nociceptors at latent MTPs are sensitized (peripheral sensitization) 16 and, in addition, could indicate a subclinical manifestation of central sensitization as larger referred pain areas are seen in, eg, fibromyalgia 15 or whiplash 32 patients with central sensitization.…”
Section: Local and Referred Muscle Pain From Nociceptive Stimulation supporting
confidence: 67%
“…Latent trigger points may appear in persons with musculoskeletal pain and may lead to muscle weakness, restricted movement, distorted muscle movement patterns, stiffness and weakness of the affected muscle4 ) . Latent trigger points may develop into active trigger points over time3, 5 ) .…”
Section: Introductionmentioning
confidence: 99%